Recomendação de especialistas para novatos em projetos de software livre baseada em suas contribuições - Santos, Erick William dos (2014)
Open source software projects require the participation of collaborators in order to achieve success. However, such collaborators work on a voluntary basis, without a formal association with the project, based only on personal and community interests. For new developers – newcomers –, it is particulary important the reception of the community that drives the project. In this work, a recommendation mechanism has been developed to select experienced developers to mentor newcomers. The conceived algorithm considered temporal aspects, aiming at reducing the withdraw ratio of newcomers due to lack of support or initial mentoring in the project.